REASSESSING ABSOLUTE JURISDICTION: LEGAL ACCOUNTABILITY AND INSTITUTIONAL IMMUNITY OF INDONESIA’S CONSTITUTIONAL COURT - Abdul Rohman; Neni Ruhaeni; Efik Yusdiansyah; Nurul Chotidjah (Al-Adl : Jurnal Hukum, 2025)
As the guardian of the constitution, Indonesia’s Constitutional Court (MK) exercises absolute judicial authority, with decisions that are final and binding. However, in practice, the Court also performs institutional administrative actions, such as appointing officials and managing internal structures. This study examines the jurisdictional boundary between the Court’s judicial and administrative functions, questioning whether the latter can be subject to administrative judicial review before the Administrative Court (PTUN). Using a normative legal approach supported by a case study (Decision No. 604/G/2023/PTUN.JKT) and comparative analysis from Germany, India, and South Korea, the study finds that constitutional immunity does not extend absolutely to administrative actions of judicial bodies. Administrative decisions that are concrete, individual, and have legal consequences must adhere to the principles of administrative law and good governance (AAUPB). The findings highlight the importance of a functional distinction between judicial and administrative authority and emphasize the need for legal oversight to ensure accountability of constitutional bodies in a democratic rule of law state.